2014
DOI: 10.5796/electrochemistry.82.351
|View full text |Cite
|
Sign up to set email alerts
|

Surface X-ray Scattering of Pd(110) and Pd(311) in Electrochemical Environments

Abstract: (311) is larger than that of the bulk in both Ar and O 2 saturated solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In situ surface X-ray scattering (SXS) analysis showed that the Pd single crystal electrodes have (1 © 1) structures. 16,17 Figures 2(d)-2(f ) show voltammograms of the low-index plane in 0.05 M KOH saturated with Ar. The anodic peak at 0.5 V (vs. RHE) of Pd(100) is due to the release of the absorbed hydrogen, and the other anodic peak is due to oxide formation.…”
Section: Liohmentioning
confidence: 99%
“…In situ surface X-ray scattering (SXS) analysis showed that the Pd single crystal electrodes have (1 © 1) structures. 16,17 Figures 2(d)-2(f ) show voltammograms of the low-index plane in 0.05 M KOH saturated with Ar. The anodic peak at 0.5 V (vs. RHE) of Pd(100) is due to the release of the absorbed hydrogen, and the other anodic peak is due to oxide formation.…”
Section: Liohmentioning
confidence: 99%
“…These peaks are related to the adsorption/desorption of (bi)sulfate anions on the wide terrace according to the study of infrared reflection absorption spectroscopy (IRAS). 18 No redox peaks on Pd(110) are attributed to the narrow terrace width of Pd(110) (1 © 1) structure 19 where (bi)sulfate anions are hardly adsorbed at lower potentials. 18 The onset potential of anodic peak of Pd oxides formation increases as Pd(110) (0.85 V) < Pd(100) (0.90 V) < Pd(111) (1.1 V).…”
Section: Resultsmentioning
confidence: 99%
“…31 Structures of adsorbed iodine were determined on Pd(111), Pd(100) and Pd(110) in 0.05 M H 2 SO 4 using STM, 32 however, real surface structures of bare Pd(100) and Pd(110) were not known in electrochemical environments. We determined real surface structures of Pd(111), Pd(100), Pd(110) 33 and Pd(311) 34 in 0.1 M HClO 4 using in-situ SXD. All the Pd surfaces examined have unreconstructed (1 © 1) structures.…”
Section: Introductionmentioning
confidence: 99%